Advanced PIC microcontroller projects in C : from USB to ZIGBEE with the 18F series - Ibrahim, Dogan (Newnes/Elsevier, 2008)
"Microchip's PIC18 offers a world of possibilities from LEDs to voltmeters to real-time operating systems (RTOSs). Filled with projects, this book starts the reader with an overview of the basic features of microcontrollers followed by a review of the PIC18 series in depth. Also included is a brief tutorial on the C programming language. The mikroC compiler is used throughout the book with a chapter devoted to its functions and libraries. Currently available development kits are discussed including simulators, emulators, and in-circuit debuggers with examples of what these tools can bring to a project. All of this is in preparation for the challenging projects that you will find between these covers."--Jacket.